2012
DOI: 10.1002/art.33493
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, tolerability, and preliminary efficacy of paquinimod (ABR‐215757), a new quinoline‐3‐carboxamide derivative: Studies in lupus‐prone mice and a multicenter, randomized, double‐blind, placebo‐controlled, repeat‐dose, dose‐ranging study in patients with systemic lupus erythematosus

Abstract: Objective. To assess the efficacy of paquinimod, a new immunomodulatory small molecule, in a murine lupus model, and to evaluate its pharmacokinetics and tolerability in systemic lupus erythematosus (SLE) patients at doses predicted to be efficacious and safe and determine the maximum tolerated dose.Methods. The efficacy of paquinimod was studied in lupus-prone MRL-lpr/lpr mice and compared with that of established SLE treatments. Dose-response data and pharmacokinetic data were used to calculate effective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 35 publications
4
94
0
Order By: Relevance
“…This inhibitor has been granted orphan medicinal product status in Europe and the US for the indication of systemic sclerosis. Importantly, ABR-215757 has been reported to have few side effects and encouraging pharmacokinetics in early-phase trials in people with systemic lupus erythematosus (68). Importantly, we now show that this molecule inhibited atherogenesis in a preclinical model of diabetes, providing a potential new therapeutic approach to reduce the cardiovascular burden in diabetes.…”
Section: 4mentioning
confidence: 63%
“…This inhibitor has been granted orphan medicinal product status in Europe and the US for the indication of systemic sclerosis. Importantly, ABR-215757 has been reported to have few side effects and encouraging pharmacokinetics in early-phase trials in people with systemic lupus erythematosus (68). Importantly, we now show that this molecule inhibited atherogenesis in a preclinical model of diabetes, providing a potential new therapeutic approach to reduce the cardiovascular burden in diabetes.…”
Section: 4mentioning
confidence: 63%
“…Recently, the S100A9 protein was identified as one molecular target of the Q-compound paquinimod (ABR-215757) [40]. We have previously shown that paquinimod interferes with development of disease both in mouse models of multiple sclerosis [40,41] and systemic lupus erythematosus [42]. Further, our previous work indicated that this compound interfered with the accumulation of myeloid cells during inflammation [43].…”
Section: Introductionmentioning
confidence: 99%
“…S100A8/A9 is of particular interest as a possible therapeutic target for the prevention of acute CV events because compounds that block the binding of S100A8/A9 to its receptors have been developed and are already approved for clinical testing in humans. 39,40 …”
mentioning
confidence: 99%